The effect of government expenditure on human capital in the Czech Republic - Linhartová, Veronika (My University, 2020)
In current thinking, human capital is referred to as a driver of national economies. It encompasses all of the knowledge, talents, skills, abilities, experience, intelligence, and training of a country's workforce. National governments are fully aware of this, and they are seeking to stimulate human capital and encourage its development. A number of studies have shown that public investment for developing human capital is claimed to be the highest performing investment for achieving better economic performance. The aim of this paper is to verify whether government investment in areas that develop human capital can indeed aid its development in the Czech Republic. Using the least squares method, the paper studies whether the Human Development Index showed correlation to individual types of government expenditure between 1995 and 2018. The analysis revealed that in the Czech Republic, spending on recreation, culture, and religion had the largest influence on developing human capital for the period under review. Expenditure on education and health, which most studies cite as the main tools for cultivating human capital, placed only third or fourth regarding their contribution to developing human capital.
Vliv veřejných výdajů na lidský kapitál v České republice
Keywords: economic growth; COFOG; human development index; public expenditures; creative labor; creative economy